PENGARUH PENGGUNAAN MEDIA SMART RULER DALAM MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN ANAK DENGAN HAMBATAN INTELEKTUAL - Khusna, Nurul; Abadi, Reza Febri; Sidik, Sistriadini Alamsyah (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2024)
This study aims to improve initial writing skills by using the Smart Ruler media.  Beginning writing according to the experts above, it can be concluded that early writing is a complex activity that includes arm, hand, finger and eye movements in order to describe / describe a language symbol (symbol) that expresses thoughts and feelings in written form and early writing is focused  on letter writing.  This study is an experimental study with a Single Subject Research (SSR) research approach, while the design used is the ABA design with a condition length of 4 - 8 - 4. In this study the target behavior to be achieved is that children can write letters, the subjects in this study are  students with mild intellectual disabilities in grade III SD at SKh Bina Citra Anak.  The research data obtained are presented in descriptive static form through graphs and percentages.  The results showed that the use of Smart Ruler media could improve the initial writing ability of students with intellectual disabilities, this was based on an increasing graph such as the percentage gain from baseline-1 (A1) by 33%, intervention (B) 74% reaching and baseline-  2 (A2) by 46%.  This can answer the problem formulation that has been formulated previously that the use of Smart Ruler media is effective in improving initial writing skills.